2021
DOI: 10.1002/jcsm.12889
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolic signatures predict recovery from thyrotoxic myopathy in patients with Graves' disease

Abstract: Background Thyroid hormone excess induces protein energy wasting, which in turn promotes muscle weakness and bone loss in patients with Graves' disease. Although most studies have confirmed a relationship between thyrotoxicosis and muscle dysfunction, few have measured changes in plasma metabolites and immune cells during the development and recovery from thyrotoxic myopathy. The aim of this study was to identify specific plasma metabolites and T-cell subsets that predict thyrotoxic myopathy recovery in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…We selected treatment period for 12 weeks. Because we previously published a paper about thyrotoxic myopathy in patient with GD [ 14 ]. In that paper, we found that skeletal muscle function and thyroid hormone levels were recovered in most GD patients treated with methimazole for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected treatment period for 12 weeks. Because we previously published a paper about thyrotoxic myopathy in patient with GD [ 14 ]. In that paper, we found that skeletal muscle function and thyroid hormone levels were recovered in most GD patients treated with methimazole for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Details have been described previously [ 14 ]. Briefly, for whole metabolite extraction, 10 µL of plasma was added to 240 µL of water and 250 µL of ice-cold methanol before being vortexed and centrifuged (14,000 ×g, 4°C, 15 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…These findings have profound diagnostic implications, since symptoms of DM2 and a variety of AIDs often overlap, like in the case of Hashimoto or Graves that can give rise to myopathy and myotonia ( 12 , 13 ). This can result in earlier diagnosis of DM2 on the one hand or lead to DM2 being completely missed, since myotonia and myopathy might be interpreted as part of a thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…The AIDs seen exclusively in the Dutch patient sample included aplastic anemia, uveitis anterior, Churg-Strauss syndrome, and autoimmune hepatitis, while the Serbian database included myasthenia gravis, neuromyelitis optica, celiac disease, and psoriasis. These findings have profound diagnostic implications, since symptoms of DM2 and a variety of AIDs often overlap, like in the case of Hashimoto or Graves that can give rise to myopathy and myotonia (12,13). This can result in earlier diagnosis of DM2 on the one hand or lead to DM2 being completely missed, since myotonia and myopathy might be interpreted as part of a thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further studies are needed to clarify the role of sclerostin in the muscle-bone relationship in a variety of racial and ethnic populations. Since it has been recognized that many hormones and growth factors regulate muscle mass and protein metabolism [ 7 , 11 , 12 ], it would be valuable to investigate the role of sclerostin in the myopathies of endocrine disorders.…”
mentioning
confidence: 99%